1982
DOI: 10.1093/ije/11.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Patterns among US Veterinarians, 1947–1977: An Expanded Study

Abstract: Causes of death among 5016 white male veterinarians identified from obituary listings in the Journal of the American Veterinary Medical Association were compared to a distribution based on the general US population. Proportions of deaths were significantly elevated for cancers of the lymphatic and haematopoietic system, colon, brain, and skin. Fewer deaths were observed than expected for cancers of the stomach and lung. Although socio-economic and methodological factors may be involved, the patterns suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 0 publications
6
40
1
2
Order By: Relevance
“…Similar observations have been reported in the USA (Botts and others 1966, Schnurrenberger and others 1977, Blair and Hayes 1980, 1982, Miller and Beaumont 1995), Australia (Jones-Fairnie and others 2008) and Norway (Hem and others 2005). …”
Section: Introductionsupporting
confidence: 88%
“…Similar observations have been reported in the USA (Botts and others 1966, Schnurrenberger and others 1977, Blair and Hayes 1980, 1982, Miller and Beaumont 1995), Australia (Jones-Fairnie and others 2008) and Norway (Hem and others 2005). …”
Section: Introductionsupporting
confidence: 88%
“…In reality, some white collar workers may be exposed to such agents. For example, physicians, other health care workers, and vetcrinarians were found to have increased leukemia risk in this study and others [Blair and Hayes, 1980;Lewis, 19631, and may encounter agents including ionizing radiation, antineoplastic drugs, and viruses. Computer scientists may be exposed to above-background levels of electromagnetic radiation, which previous studies indicate may be an occupational leukemogen [Savitz and Calle, 19871, and also had excess leukemia tnortality , although electricians and electric power installers did not.…”
Section: Discussionsupporting
confidence: 57%
“…The hypothesis that a leukemogenic agent is present in slaughterhouses is supported by the finding that veterinarians employed as meat inspectors also have an increased risk for lymphatic and hematopoietic cancers (41). Epidemiologic evidence for the role of zoonotic viruses in human cancer is currently weak, although some studies have found associations between various hematologic malignancies and farming (40).…”
Section: Discussionmentioning
confidence: 99%